Role of food protein-derived peptides in the treatment of colon cancer - Xue Deng; Jing Yang; Huayi Suo; Jiajia Song (Food Science of Animal Products)
Colon cancer is one of the leading causes of cancer-related deaths and the second most common cancer in Western countries. Despite the availability of various treatment modalities, these therapies have not been fully successful due to their limited effectiveness and serious side effects. As a result, an increasing number of researchers are focusing on the search for natural active substances as potential agents for the treatment and prevention of colon cancer. Bioactive peptides derived from proteins play an important role in maintaining body functions. Several in vivo and in vitro studies have demonstrated that protein peptides can help prevent and mitigate colon cancer. This paper, therefore, explores the mitigating effects and mechanisms of action of protein peptides from different sources on colon cancer, as well as the factors influencing their anticancer effects. It provides a scientific basis for the prevention and treatment of colon cancer and for the development of new raw materials for foods with potential anticancer properties.